Nanogold: a quantitative phase map. - Barnard, A; Young, N; Kirkland, A; Huis, v; Xu, H (2009)
The development of the next generation of nanotechnologies requires precise control of the size, shape, and structure of individual components in a variety of chemical and engineering environments. This includes synthesis, storage, operational environments and, since these products will ultimately be discarded, their interaction with natural ecosystems. Much of the important information that determines these properties is contained within nanoscale phase diagrams, but quantitative phase maps that include surface effects and critical diameter (along with temperature and pressure) remain elusive. Here we present the first quantitative equilibrium phase map for gold nanoparticles together with experimental verification, based on relativistic ab initio thermodynamics and in situ high-resolution electron microscopy at elevated temperatures.